The role of cash waqf in poverty reduction : a case study of Somalia - Salad, Abdiwali Jama (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Poverty is one of the problems affecting many countries in the Muslim world. Fighting against poverty and alleviating it from the societies is imperative. The issue of poverty does not only rely on economic and social policies, population size and resource endowments, but also on the types of economic undertakings that are being embark up on. What is important is the kind of policies, that are put forward to eliminate poverty, and to what degree their executions are adequately fruitful in achieving the objectives. With that, one of the primary objectives of the shariah is poverty alleviation, establishment of socio-economic justice and equitable distribution of wealth. Cash waqf is a viable type of Islamic endowments whose objective is to provide relief to the less fortunate citizens among societies. This research explores that, the faith based endowments potential to reduce the poverty level in Somalia as was the case in the glorious ages of Islamic civilization. Waqf in Somalia, throughout the history has not contributed to the development in all sectors. There are no functioning endowment institutions in Somalia, that take care waqf properties and register it legally. Even though, waqf history in Somalia is as old as the arrival of Islam, the perception of the society towards waqf is solely for religious purposes. This study adopts qualitative method, it relies on information sourced from previous literature, Quran, Hadith, working papers and internet sources. It is critically analyzed the existing cash waqf models in some Muslim and Muslim minority countries in relation with the socio-economic situation of Somalia. In line with this, the study adopted the waqf shares scheme. This scheme seems to be fitting Somalia for several important reasons. It is relatively easy to raise fund from public via traditional way of collecting money by cash or by mobile payment system, which is widely used in Somalia. it is argued that, the fund generated can be used for creation of employment opportunities and as a result, many poor Somalis will be empowered financially, socially and educationally. Finally, the result of this study shows that, cash waqf is viable and able to reduce poverty among less-privileged Somalis.